A modified model for calculating crack tip opening displacement (CTOD) considering fracture process zone (FPZ) in rock - Yang Qiao; Zong-Xian Zhang; Jun Zhou (Geomechanics and Geophysics for Geo-Energy and Geo-Resources, 2024)
Abstract A new CTOD calculation method is investigated in this study, considering the FPZ and the effective Young’s modulus. The calculated CTOD values from four theoretical models are compared with the measured CTOD values from the three-point beam experiments, and the differences between them are analyzed. The measured CTOD consists of two parts: (1) the displacement generated by the elastic–plastic deformation in the crack tip region, and (2) the displacement generated by micro-damage in the FPZ. CTOD value caused by micro-damage in the FPZ accounts for 81–92% of the overall CTOD. Thus, the FPZ and the effective Young’s modulus are introduced to modify the models for calculating CTOD. The result indicates that the modified plastic zone model is better than the strip-yield model, the plastic zone model and the modified strip-yield model in calculating CTOD, and CTOD error is reduced from 81 to 90% between the plastic zone model and the experiment to 4–34% between the modified plastic zone model and the experiment, with nearly half of the specimens having an error of less than 10%.